Hubungan Motivasi Belajar dengan Prestasi Belajar Siswa pada Mata Pelajaran Ekonomi Kelas X (Sepuluh) di MA Al-Qurtubiyyah Nagrak Tahun Pelajaran 2016/2017 - Ahmad Riyadi; Sayyidia Shofara Alhanif (Fakultas Syariah IAIN Laa Roiba Bogor, 2020)
ABSTRACT .This study aims to examine the relationship between student learning motivation and student learning Achievement in economic subjects class X (Ten ) at MA Al-Qurtubiyyah Nagrak Academic Year 2016/2017. To obtain “X” variable data